Antibacterial Activity of Crude Extracts of Spirulina Platensis Against Some Pathogenic Bacteria and Fungi Isolated from Different Sites on Human Body - Intesar Kareem Abdul Hassan1, Ammar Adnan Tuama1, Khamael Ali Kareem1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Spirulina platensis are filamentous, undifferentiated, non-toxigenic cyanobacteria that have been used as food since ancient times. There have been numerous studies on its antioxidant and antimicrobial actions. Spirulina as many other cyanobacteria species have the potential to produce a large number of antimicrobial substances, so they are considered as suitable organisms for exploitation as biocontrol agents of plant pathogenic bacteria and fungi. In the present study, antimicrobial activity of Spirulina platensis solvent extracts in serial dilution was investigated against pathogenic bacteria and fungi. The antimicrobial activity of Spirulina platensis was determined against pathogenic bacterial and fungal isolates. The methanol extract of Spirulina platensis showed maximum zone of inhibition against all the bacterial and fungal isolates.